Pengembangan Media Pembelajaran Sistem Saraf Dengan Menggunakan Adobe Flash CS3 pada Siswa Kelas XI Sekolah Menengah Atas - Dian Arisetya; Ely Djulia; Hasruddin Hasruddin (Jurnal Pendidikan Biologi, 2016)
This study was intended to: (1) identify the development of learning media procedure nervous system with Adobe Flash CS3 for XI grade high school student; (2) figure up the student’s responds to learning media development of nervous system with Adobe Flash CS3 for XI grade high school student. This study was classified as Borg & Gall model development that included to 6 steps (1) Information collection; (2) Designing; (3) pre-product development; (4) expert validation; (5) revision; (6) post product testing. The subject of this research was XI grade high school student of SMA N 1 Rantau Selatan LabuhanBatu at 2012/2013 academic year. This study was designed by questionnaire method (Linkert scale) that administered for testing to two media experts, two matter experts, three personals, 9 small groups, and 30 bounded field. The collected data was analyzed by applying descriptive analysis, qualitative analysis and   inferential analysis by employing SPSS version software 19.0 for Windows. The analysis revealed the test by (1) learning media experts (89%); (2) learning biology matter expert (83%); (3) personal (83%); (4) small groups (91%); (5) bounded field (94%). The scores indicate that responses from media experts, matter experts and student to biology learning media development with Adobe Flash CS 3 for nervous system for high school student is very good categorized.